Carbon storage and carbon pool characteristics of Larix gmelinii forest in Daxing’anling, Inner Mongolia, China - Zhao, Kai; Yue, Yongjie; Qin, Fucang; Hai, Long; Yi, Lixi; Zhao, Pengwu; Hao, Longfei; Shu, Yang; Zheng, Yaxiong; Li, Long; He, Rong; Xu, Yajie (Frontiers in Forests and Global Change, 2024)
Larix gmelinii is an important ecological construction tree species in northern China, and its carbon storage and distribution characteristics are of great significance for evaluating the carbon balance and climate effect of forest ecosystems. However, at present, there is a lack of systematic research on the carbon storage of L. gmelinii forests and its change with forest age. In this paper, the biomass and carbon density of L. gmelinii forests at different ages and the distribution of carbon storage in vegetation and soil were analyzed by means of sample plot investigation and model simulation in the northern forest area of Daxing'anling, Inner Mongolia. The influence of forest age on the carbon storage and carbon pool distribution characteristics of L. gmelinii forests and the mechanism of influencing factors were also discussed. Results show that: (1) As forest age increased, the total amount of carbon pools initially increased and then decreased, and the distribution structure of carbon pools showed a trend of transferring from soil to trees. The proportion of soil carbon pools gradually decreased (72.72%-51.87%), while the proportion of tree carbon pools gradually increased (23.98%-39.33%). The proportion of shrub and grass carbon pools was also relatively stable (0.51%-0.53%). (2) Soil carbon pool was affected by the input and output of soil organic matter, soil depth, soil carbon content, and soil bulk density, shrub-grass carbon pool was affected by undergrowth light conditions and soil moisture, litter carbon pool was affected by litter input and output, and the carbon pool of trees was affected by the growth rate and carbon balance of trees. This study provides scientific basis and management suggestions for the carbon storage capacity of L. gmelinii forests and the mitigation of climate change.